Multiplayer online role-playing as information retrieval and system use: an ethnographic study. Issue 3 (24th January 2018) - Harviainen, J. Tuomas; Rapp, Amon
Abstract : Purpose: The purpose of this paper is to expand the research of games as information systems. It illustrates how significant parts of massively multiplayer online role-playing function like information retrieval from a library database system. Design/methodology/approach: By combining ideas from earlier contributions on the topics of game environments as information systems, the paper explores how gameplay connects to information retrieval, restricted content access, and information system structure. The paper then proceeds to examine this idea through an ethnographic study conducted in World of Warcraft during 2012-2016. Findings: By discussing how multiplayer digital game play is a form of information retrieval, the paper shows that players enjoy the well-restricted access to information that is a constitutive element of gameplay. Examining controlled access, procedural literacies and emphatic keywords, the paper finds that content relevances and system use may be influenced by hedonic concerns rather than task efficiency. Originality/value: The study of retrieval issues related to gaming enriches our knowledge on inferences in retrieval. It shows that people may prefer that their access to information be limited, in order to make system use more interesting.